2021
DOI: 10.1111/ssm.12505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of confirmation and structured inquiry on attitudes toward school science

Abstract: Scientific inquiry has a prominent status in science education. Research on the effect of inquiry-based science teaching on attitudes toward science abounds (Aguilera & Perales-Palacios, 2020;Demirel & Dağyar, 2016). Studies show promising results for inquiry strategies offering the least teacher guidance. Yet such approaches present drawbacks and constraints when enacted by teachers, such as time and classroom management issues, limited resources, and lack of pedagogical content knowledge (Baroudi & Helder, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…In fact, this situation manifests itself more clearly in the studies of groups consisting of only men. The findings of the study suggest that inquiry-based learning does not make a significant difference in the attitudes of female and male students towards science (Saylan Kırmızıgül, 2019;Tatar, 2006;Toma, 2021). As a result, doing a study on how inquiry-based learning settings backed by various instructional technologies might result in a large improvement in men's attitudes is deemed crucial.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, this situation manifests itself more clearly in the studies of groups consisting of only men. The findings of the study suggest that inquiry-based learning does not make a significant difference in the attitudes of female and male students towards science (Saylan Kırmızıgül, 2019;Tatar, 2006;Toma, 2021). As a result, doing a study on how inquiry-based learning settings backed by various instructional technologies might result in a large improvement in men's attitudes is deemed crucial.…”
Section: Discussionmentioning
confidence: 95%
“…Inquiry activity improves students' positive attitudes towards science learning (Gibson & Chase, 2002;Habelliaa & Suyantaa, 2019;Sangkala & Doorman, 2019). Studies report that students' attitudes and interests increase after participating in the inquiry activity draw attention (Toma, 2021;Tuan et al, 2005). Students who learn how it feels when a question completely occupies the mind in the classroom environment can carry the effect of this feeling to their daily lives (Bruner, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…RIED-Revista Iberoamericana de Educación a Distancia, 27(2). https://doi.org/10.5944/ried.27.2.39109 (Osborne, 2014;Pedaste et al, 2015;Toma, 2021a). Por ello, aunque coexisten varias interpretaciones y definiciones de la indagación, su uso pedagógico implica que los estudiantes emulen el quehacer de los científicos.…”
Section: Fundamentos Teóricos Enseñanza De Las Ciencias Por Indagaciónunclassified
“…Instead, this investigation considered confirmation and structured inquiry as a whole, cohesive program or approach, thus aligning with long-standing definitions from the literature and existing studies comparing types of inquiry (e.g., Bunterm et al, 2014;Sadeh & Zion, 2012;Schmid & Bogner, 2017). A previous study that focused on this topic found no benefit of confirmation and structured inquiry in improving elementary students' attitudes towards science (Toma , 2022). Hence, this investigation advances in this line of research by specifically addressing the following research question:…”
Section: Introductionmentioning
confidence: 97%